PEMILIHAN METODE PERHITUNGAN PENGURANGAN EMISI KARBON DIOKSIDA DI SEKTOR TRANSPORTASI - Dimas Bayu Endrayana Dharmowijoyo; Ofyar Zainuddin Tamin (Jurnal Transportasi, 2010)
Climate change issues in the world is a problem that needs attention. In the last three wasrsa dasa, has been an increase of carbon dioxide in the air is very large, reaching about 70%. Carbon dioxide emissions have resulted in the Greenhouse Effect, which causes climate change, both in local and global scale. Meriupakan transport sector one of the sectors that contributed to the increase in carbon dioxide emissions. Furthermore, the Intergovernmental Panel on Climate Change (IPCC) states that there are three main sectors that affect theincrease in carbon dioxide emissions within 30 years, namely the transport sector, energy supply sector, and industrial sectors. Carbon dioxide emissions can be calculated using various methods available and seytiap method requires the data obtained in various ways. In this study the selection method of calculating carbon dioxide emissions generated by the transportation sector. From this study found that the method of using vehicle kilometer travel is the most suitable method for the conditions in Indonesia.Keywords: transport emissions, carbon dioxide emissions, vehicle kilometer travel